Anticancer effects and mechanisms of Pulsatilla chinensis, Bupleurum chinense and Polyporus umbellatus on human lung carcinoma and hepatoma cells - Mengzhen Li; Woonghee Kim; Han Jin; Hong Yang; Xiangtai Kong; Xiya Song; Hasan Turkez; Yuefeng Bi; Chengxue Pan; Ling Fu; Hongmin Liu; Mathias Uhlen; et al. (Computational and Structural Biotechnology Journal, 2025)
Herbs are extensively utilized in Traditional Chinese Medicine (TCM) for lung and liver cancer treatment, but the mechanisms behind these herbs remain largely unknown. Here, high-throughput transcriptomic analysis technology was used to uncover molecular mechanisms of herbal treatment. Furthermore, we developed a compound recognition approach utilizing the LINCS L1000 database to identify potential treatment targets. Our results showed that among 14 herbs tested, Pulsatilla chinensis exhibited the strongest anticancer effects in A549 and Huh7 cells, followed by Bupleurum chinense, and Polyporus umbellatus. P. chinensis exerts its anticancer properties by downregulating cell cycle-related transcription factors, including E2F1 and TFDP1. Notably, the mechanisms of P. chinensis treatment differed between the two cell lines. In A549 cells, which possess wild-type p53, P. chinensis induced apoptosis through the regulation of the p53 pathway. In contrast, in Huh7 cells, which harbor mutant p53, the effect was mediated via the TNF-α/NF-κB signaling pathway. We also identified two drugs, AMG232 and Nutlin-3, that exhibited treatment effects similar to P. chinensis in A549 cells. Both drugs function as inhibitors of the MDM2-p53 interaction. Western blot analysis confirmed the alteration of the relevant proteins, aligning with our computational predictions. Furthermore, 23-hydroxybetulinic acid, a key active compound of P. chinensis, demonstrated the ability to inhibit the p53-MDM2 interaction by binding to the same pocket on the MDM2 protein.